ANALISIS DETERMINAN RISIKO INVESTASI SAHAM (Studi Kasus pada 10 Bank Umum Swasta Nasional Terbesar yang Terdaftar di Bursa Efek Indonesia) - Sitanggang, Widya Siska (Jurnal Ilmiah Mahasiswa FEB, 2015)
This research aims to analyze the effect of economic conditions, which is inflation and the interest rate of Bank Indonesia and fundamental factors which is LDR, CAR, and the NPL against the risk of investment shares. The data of this research in the form of quarterly time series data from January 2010 until December 2014. The analysis techniques will be used in this research is the regression of the data panel. The results of this study indicate that a variable inflation, interest rates of Bank Indonesia, and NPL have positive effect that significant to risk of stock investment. While variable LDR and CAR have no significant effect to risk of stock investments. Â  Keywords: risk stocks, inflation, interest rates of Bank Indonesia, LDR, CAR, NPL